Human Resource Management Journal: A look to the past, present, and future of the journal and HRM scholarship. (17th December 2019) - Farndale, Elaine; McDonnell, Anthony; Scholarios, Dora; Wilkinson, Adrian
Abstract: This editorial lays out 30 years of history of Human Resource Management Journal ( HRMJ ), charting the journal's roots, reflecting on HRM scholarship today and guiding authors on potential contributions to the journal in the future. HRMJ has achieved high recognition and ranking internationally since its conception originally as a UK‐based journal. The journal's broad‐based approach to the study of the management of people at work, means it appeals to scholars from a multitude of disciplines, not least of all management, industrial relations, psychology and organisational behaviour. HRMJ is also highly rigorous in its review process, ensuring reliable, interesting and impactful articles that further our knowledge of theory and practice.